2022
DOI: 10.3390/jcm11051431
|View full text |Cite
|
Sign up to set email alerts
|

The GenoDiabMar Registry: A Collaborative Research Platform of Type 2 Diabetes Patients

Abstract: The GenoDiabMar registry is a prospective study that aims to provide data on demographic, biochemical, and clinical changes in type 2 diabetic (T2D) patients attending real medical outpatient consultations. This registry is also used to find new biomarkers related to the micro- and macrovascular complications of T2D, with a particular focus on diabetic nephropathy. With this purpose, longitudinal serum and urine samples, DNA banking, and data on 227 metabolomics profiles, 77 immunoglobulin G glycomics traits, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The GenoDiabMar study is a type 2 diabetes adult registry recruited between 2012 and 2015 from the healthcare area Litoral-Mar of Barcelona, Spain. 17,18 Patients older than 45 years with a medical history of type 2 diabetes for more than 10 years and treated with anti-diabetic drugs were included (n = 640 for the current study).…”
Section: Patient Cohortsmentioning
confidence: 99%
See 3 more Smart Citations
“…The GenoDiabMar study is a type 2 diabetes adult registry recruited between 2012 and 2015 from the healthcare area Litoral-Mar of Barcelona, Spain. 17,18 Patients older than 45 years with a medical history of type 2 diabetes for more than 10 years and treated with anti-diabetic drugs were included (n = 640 for the current study).…”
Section: Patient Cohortsmentioning
confidence: 99%
“…Definitions for vascular complications have been described in detail for DiaGene, Geno-DiabMar and DCS cohorts. 15,16,18 In short, retinopathy for all studies was scored by an ophthalmologist based on fundus photography, and for the current study was defined as present or absent, where present includes all gradations and stages of diabetic retinopathy. Nephropathy was defined as microalbuminuria [albumin/creatinine-ratio (ACR) ≥2.5 mg/mmol for men or ≥3.5 mg/mmol for women] present at two of three consecutive measurements or when high micro-albuminuria or macro-albuminuria was present at one measurement (ACR ≥ 12.5 mg/ mmol for men or ≥17.5 mg/mmol for women).…”
Section: Measurements and Definitions Of Macro-and Microvascular Comp...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, diabetes mellitus was considered as the leading cause of chronic kidney disease and caused approximately 1.5 million deaths in 2016 ( 3 ). Moreover, previous clinical studies demonstrated that the cardiovascular mortality rate of patients with diabetic nephropathy (DN) was significantly higher than that of patients without DN ( 4 , 5 ); thereby, DN may be related to macrovascular lesions and promote AS to a certain extent.…”
Section: Introductionmentioning
confidence: 99%